2014
DOI: 10.1007/s00339-014-8950-x
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric property determination of hybrid Al2O3-filled MWCNT buckypaper by the rectangular cavity perturbation technique

Abstract: This study investigated the complex dielectric permittivity of freestanding multiwalled carbon nanotube buckypaper (MWCNT-BP) and a synthesized hybrid alumina-filled buckypaper (Al 2 O 3 -BP) composite with different alumina loadings (5-30 wt%). The non-destructive microwave transmission technique for complex permittivity determination involving cavity perturbation was employed to characterize a set of Al 2 O 3 -BP sheets. This was done by filling a rectangular cavity resonator with a standard dielectric Teflo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
1
0
0
Order By: Relevance
“…3(e) it was observed that the nanotubes form a cluster in the 0.05 wt% MWCNT containing the sample and this can be attributed to the agglomeration of nanotubes due to the van der Waals force. 35 A similar morphological pattern was discovered for gel-based carbon nanotube composite films where CNTs form a bundle at higher concentrations. 36 Also, MWCNTs were wrapped with gelatin by the different functional groups of its polymer chain during the sonication process which helps them to disperse evenly throughout the polymer matrix.…”
Section: Resultssupporting
confidence: 61%
“…3(e) it was observed that the nanotubes form a cluster in the 0.05 wt% MWCNT containing the sample and this can be attributed to the agglomeration of nanotubes due to the van der Waals force. 35 A similar morphological pattern was discovered for gel-based carbon nanotube composite films where CNTs form a bundle at higher concentrations. 36 Also, MWCNTs were wrapped with gelatin by the different functional groups of its polymer chain during the sonication process which helps them to disperse evenly throughout the polymer matrix.…”
Section: Resultssupporting
confidence: 61%